Digital Business as a Field for Research and Education - Thomas Hess; René Riedl; Luc Becker (Electronic Markets, 2024)
Digital technologies ignite new businesses and force existing companies to restructure their business models. Various independent academic research streams discuss the potential of digital technologies for business. However, these streams' research findings are published across outlets in various communities, and an approach to bringing these streams together is missing. In this position paper, we propose to integrate these streams under the concept of Digital Business . We see Digital Innovations as the core of Digital Business and offer a framework for structuring the field. Using this framework, we describe the field's development to date and provide three ideas for further integrating the field in the future. Altogether, a key aim of this paper is to create a conceptual basis that structures both research and education in the field Digital Business .
Keywords: M15; 620; Digital Business; Digitalization; Digital Transformation; Digital Innovations; Electronic Business